1998
DOI: 10.1128/iai.66.4.1638-1647.1998
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation of NF-κB in Lipopolysaccharide-Treated Macrophages Fails To Correspond to Endotoxicity: Evidence Suggesting a Requirement for a Gamma Interferon-Like Signal

Abstract: Elucidation of a signal transduction pathway essential to lipopolysaccharide (LPS)-induced macrophage activation has the capacity to provide new targets for the treatment of septic shock. In this regard, activation of the transcription factor NF-κB is commonly thought to be critical to LPS-stimulated macrophage inflammatory mediator production, although certain immunological, genetic, and molecular evidence suggests that other factors are involved. To address this issue, we hypothesized that the degree of LPS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Interleukin-1or gamma interferon-specific antibody did not block LPS-induced hepatic injury, which suggested that (i) TNF-␣ may be primarily responsible for hepatic injury and (ii) TNF-␣-induced NO production may participate in the development of hepatic injury. It was recently reported that the lethal dose of LPS in D-GalN-sensitized mice correlated with in vitro TNF-␣ and NO production in a macrophage cell line treated with the same LPS (6), which also supported our conclusions derived from the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Interleukin-1or gamma interferon-specific antibody did not block LPS-induced hepatic injury, which suggested that (i) TNF-␣ may be primarily responsible for hepatic injury and (ii) TNF-␣-induced NO production may participate in the development of hepatic injury. It was recently reported that the lethal dose of LPS in D-GalN-sensitized mice correlated with in vitro TNF-␣ and NO production in a macrophage cell line treated with the same LPS (6), which also supported our conclusions derived from the present study.…”
Section: Discussionsupporting
confidence: 93%
“…21,39,40 LPS has been reported to trigger mitogen-activated protein kinases, NF-κB, STAT3, IRFs and activator protein signal-transduction pathways by the activation of the TLR4 receptor complex (TLR4/MD2), which evokes the transcription and production of immune genes, including cytokines that are critical for activation of innate immunity. 41,4244 In this study, we found that increasing TLR4 and MD2 expression was detected in both types of DCs, with higher phagocytic activity, coinciding with previous reports. 45 Similar to the other studies in mice and humans, we demonstrated that the TLR4/MD2 complex genes were up-regulated in porcine moDCs and SDCs in a time-dependent manner in response to LPS stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Systemic inflammation is a hallmark of endotoxemia ( 2 , 35 ) where multiple receptors are activated and signals converge to activate the NF-κB family of transcription factors ( 36 , 37 ). To determine the degree of inflammation in the whole larvae, an NF-κB reporter zebra fish line, Tg(NF- κ B:GFP) ( 38 ), was used, where the transcription of the GFP reporter gene is activated by NF-κB.…”
Section: Resultsmentioning
confidence: 99%